2000
DOI: 10.1097/00004045-200009000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Using Guided Imagery to Reduce Pain and Anxiety

Abstract: Guided imagery is a therapeutic technique that allows a person to use his or her own imagination to connect their body and mind to achieve desirable outcomes such as decreased pain perception and reduced anxiety. This article describes the use and application of guided imagery for clients in the home and the benefits to the agency. A step-by-step approach to teaching clients how to use guided imagery is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…We chose 30 words in response to experience in previous studies on the same EHR data set [26,27,28,29]. The snippets were categorized into 6 modalities: Acupuncture, Biofeedback, Guided Imagery [30], Meditation, Tai-Chi and Yoga. For each modality, a small subset (n=500~600) of the snippets was selected for human annotation.…”
Section: Dataset and Cih Extractionmentioning
confidence: 99%
“…We chose 30 words in response to experience in previous studies on the same EHR data set [26,27,28,29]. The snippets were categorized into 6 modalities: Acupuncture, Biofeedback, Guided Imagery [30], Meditation, Tai-Chi and Yoga. For each modality, a small subset (n=500~600) of the snippets was selected for human annotation.…”
Section: Dataset and Cih Extractionmentioning
confidence: 99%
“…Guided imagery involves the generation of specific mental images to evoke a state of relaxation or physiologic change [9], {10}, [11], such as, the imagining of pain from a headache being collected in a balloon and slowly drifting away. Although, it is difficult for some people to accept that pain can have a psychological as well as physical root, randomised-controlled studies have found that guided imagery has significantly reduced various types of pain [8]. During one session with Sally, she reported that she was suffering with pain on her spine, which almost felt like someone was "playing it like an instrument".…”
Section: Mapping Gate Theory Onto Personal Experiencementioning
confidence: 99%
“…Guided imagery has been used successfully in a variety of formats, including live guided imagery, where a health care professional speaks directly to patients, and audiorecorded guided imagery, and with both individuals and groups of patients (Eller, 1999). Guided imagery has been commended for its effectiveness, affordability, and simplicity of administration (Ackerman & Turkoski, 2000;Apóstolo & Kolcaba, 2009;Tusek & Cwynar, 2000).…”
Section: What Is Guided Imagery?mentioning
confidence: 99%